The role of isoflavones in augmenting the effects of radiotherapy - Ivashkevich, Alesia (Frontiers in Oncology, 2023)
The traditional soy diet containing isoflavones, consumed by the Asian population in China and Japan has been identified as a protective factor from hormone-related cancers. Over the years the research focus has shifted from emphasising the preventive effect of isoflavones from cancer initiation and promotion to their efficacy against established tumours along with chemo- and radiopotentiating effects. Studies performed in mouse models and results of clinical trials emphasize that genistein or a mixture of isoflavones, containing in traditional soy diet, could be utilized to both potentiate the response of cancer cells to radiotherapy and reduce radiation-induced toxicity in normal tissues. Recent clinical research has demonstrated a potential of another significant isoflavone, idronoxil, also known as phenoxodiol, as radiation enhancing agent. In the light of those recent clinical findings, this article reviews the accumulated evidence which support the clinically desirable interactions of soy isoflavones with radiation therapy resulting in improved tumour treatment. This review discusses important aspects of the development of isoflavones as anticancer agents, and mechanisms potentially relevant to their activity in combination with radiation therapy of cancer. It gives a critical overview of studies characterising isoflavone targets such as topoisomerases, ENOX2/PMET, tyrosine kinases and ER receptor signalling, and cellular effects on the cell cycle, DNA damage, cell death, and immune responses.